Analisis Usahatani Kakao Pola Swadaya Di Desa Talontam Kecamatan Benai Kabupaten Kuantan Singingi - Yuyunisari Yuyunisari; Evy Maharani; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Self-help pattern is the pattern of cocoa plantation done by the farmers where the business capital is purely from the farmers or the community themselves without the help of other parties. This research focuses on cocoa plantation in Talontam Village, where to know the cocoa farming pattern that is not yet known whether the farming can increase the income of farmers in Benai.DataSubdistrict used in this research is primary data and secondary data. This research technique used is purposive sampling. Stages of data analysis in this study include (1) Income Analysis of Cocoa Farmers Self-Supporting Patterns that calculate (farm costs, gross income, net income, and family income). (2) Analysis of the efficiency of cocoa farming self-help pattern. The results of the study with the average land area of cocoa self-help pattern with the average of 0.17 Ha cocoa area with net income (Rp.3.622.835,85 / lg / th) then cocoa farming is also feasible and efficient where the value of Return Cost Ratio ≥ 1 based on arable land 2.3. Keywords :cocoa, farming,income,self-help pattern